To the 100th anniversary of Ivan Tanasienko: in memory of a teacher, scientist, and surgeon - Tsyura, Y. P.; Kryvopustov, M. S. (General Surgery, 2025)
The article commemorates the 100th anniversary of the birth of Ivan Denisovich Tanasienko (1925—1998), an outstanding Ukrainian surgeon, teacher, scientist, and medical education organizer. The article highlights the key stages of his life, professional development, and scientific activity. I. D. Tanasienko began his career in the post‑war period as a doctor at a peripheral hospital and rose to the rank of professor at the Kyiv Medical Institute, dean of the faculty, and head of the Department of Surgery. His scientific interests encompassed a wide range of issues related to abdominal, vascular, endocrine, and emergency surgery. He was among the first in Ukraine to adopt contemporary methods of diagnosing and treating obstructive jaundice and diseases of the stomach, biliary tract, and pancreas. He authored over 100 scientific papers, spearheaded clinical innovations, and supervised 16 candidate’s and 2 doctoral theses. Ivan Denisovich, a remarkable lecturer and mentor, influenced students’ knowledge as well as their perspective, instilling strong ethical standards in medicine. His contributions to medicine were recognized with the State Prize of Ukraine. The bright memory of I. D. Tanasienko lives on in the hearts of his students, colleagues, and grateful patients.